PENINGKATAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI MATERI PEMBELAHAN SEL MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE - Nur Anisah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Madura, 2018)
The Improvement of Students’ Activity and Biology cell division material Learning Achievement Through Applying a Cooperative Learning Model Type Think Pair Share (TPS) to Students in Class XII Science of SMA Darussyahid. This study is a classroom action research aims to improve the students activities and biology learning achievement through applying a cooperative learning model type Think Pair Share (TPS). The subjects of this study were all students in class XII Science of SMA Darussyahid active during the academic year 2014/2015 which consisted of 30 students. Implementation of this study consisted of two cycles. Data collected through the observation sheets and evaluation test were analyzed by using quantitative and qualitative analysis. The results showed that the average of students activity in cycle I were 61.19% and in cycle II were 77.84%, and the average of student learning achievement were 31,25 in cycle I and became 78,82% in cycle II. Based on the result, it can be concluded that the application of a cooperative learning model type TPS can improve the activity and learning achievment of student in XII IPA Class of SMA Darussyahid.